2020
DOI: 10.1007/s11258-020-01016-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term change in calcareous grassland vegetation and drivers over three time periods between 1970 and 2016

Abstract: Analysis of long-term vegetation change is limited. Furthermore most studies evaluating change only examine two snapshots in time, which makes it difficult to define rates of change and accurately assess potential drivers. To assess longterm change in calcareous grassland over multiple time periods, we re-surveyed a transect study undertaken at Parsonage Down National Nature Reserve, Wiltshire, southern England in 1970 and 1990 by T. Wells. We examined differences in soil properties and species traits in each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 60 publications
3
22
0
Order By: Relevance
“…We also found significant reductions in insect abundance and richness in response to increasing fertiliser application rate on croplands, particularly for the hymenopterans and lepidopterans. Sensitivity to land-use for butterflies has previously been attributed to dietary specialism: relative to flies, many butterflies are known to be dietary specialists as larvae 4 , making a reduction in lepidopteran species richness and diversity likely when plant species richness is reduced, which is known to occur at high fertiliser application rates 3 , 41 . Previous research in the temperate zone has indicated beetle flower visitors are sensitive to land-use change 74 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found significant reductions in insect abundance and richness in response to increasing fertiliser application rate on croplands, particularly for the hymenopterans and lepidopterans. Sensitivity to land-use for butterflies has previously been attributed to dietary specialism: relative to flies, many butterflies are known to be dietary specialists as larvae 4 , making a reduction in lepidopteran species richness and diversity likely when plant species richness is reduced, which is known to occur at high fertiliser application rates 3 , 41 . Previous research in the temperate zone has indicated beetle flower visitors are sensitive to land-use change 74 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar indirect effects have also been shown for fertiliser application. For example, nitrogen-based fertilisers reduce plant species diversity 41 , and dispense with the requirement for clover field crop rotation, further reducing floral availability for pollinators 42 .…”
Section: Introductionmentioning
confidence: 99%
“…The impact of encroaching or "super-dominant" species on richness can be due to competitive exclusion, where taller species outcompete smaller and more slender species; for instance, in the search for light (Ridding et al, 2020). Besides, the emergence of shrubs in wet grasslands led to a greater loss of water through evapotranspiration, consequently decreasing the water available in the soil for other growth forms (Budny & Benscoter, 2016).…”
Section: Shrub and Grass Encroachmentmentioning
confidence: 99%
“…At present, area losses as a result of land‐use change are considered the greatest threat to these grasslands and their species (Sala et al, 2000; WallisDeVries et al, 2002; Pompe et al, 2011). In addition, they are negatively affected by habitat degradation due to eutrophication and a lack of management (Bobbink & Willems, 1987; Bennie et al, 2006; Diekmann et al, 2014; Bauer & Albrecht, 2020; Ridding et al, 2020).…”
Section: Introductionmentioning
confidence: 99%